The politics of giving in the Viceroyalty of Río de la Plata : donors, lenders, subjects, and citizens - Grieco, Viviana L., 1969- (University of New Mexico Press, 2014)
This book examines an eighteenth century Spanish state finance based on voluntary donations rather than taxes. The author analyzes the "gifts" (donativos) that residents of colonial Argentina gave to the Spanish Crown and the city council of Buenos Aires.